The Influence of Human Resource Competence on Service Quality for Functional Appropriate Certificates (LFS) - Andi Pattarani; Nur Ilmiah Rivai (Program Pascasarjana Universitas Negeri Makassar, 2022)
Function-worthy Certificate (LFS) is a form of government control over the strength of building construction before it is used. If the building is to be erected, it must have a Building Permit (IMB), then after the building is erected and before being used, it must have an SLF. The concept of service quality can be understood through consumer behavior in finding, buying, using and evaluating a product or service that is expected to satisfy their needs. indeed sometimes it takes a lot of time with fairly complicated requirements that must be completed by the developer or building owner. These factors influence each other in order to achieve a good qua lity of public service. Competence is the ability possessed by a person including knowledge, skills, creativity, attitude to do his job well based on work standards and procedures for providing services that have been set. The formulation of the problem in this study is how much influence employee competence has on service quality at the Makassar City DPMPTSP Office. The research methodology used is a quantitative research approach. The population is 79 samples. Purposive sampling so that the sample is 79 people. Data Collection Instruments, Observations, Questionnaires. Data Analysis Techniques Validity Test, Significance Test. Reliability test. The results of the HR Competency research have a positive and significant effect on. Quality of Service Management of Licenses for the Management of Function-worthy Certificates (LFS) at the Makassar City Investment and One Stop Integrated Services (DPMPTSP) Office. smaller than 0.05. Licensing Service for Feasibility Certificate Management (LFS) at the Investment Service and One Stop Integrated Services (DPMPTSP) with a Sig level value of 0.001 < 0.05.